Chemical characterization of wheat kernels naturally contaminated by deoxynivalenol-DON when cultivated under nitrogen management strategies - Souza, Thiago; Prando, André; Takabayashi-Yamashita, Cassia; Zucareli, Claudemir; Hirooka, Elisa (Revista Ciência Agronômica, 2019)
Chemical composition and contamination of wheat kernels (Triticum aestivum L.) directly affect the quality of the flour obtained from them, determining its acceptability and use by industry. Field trials were conducted to evaluate the effect of agricultural practices on wheat kernel quality (chemical composition and contamination). Cultivation was carried out following maize or soybean (crop succession), with application of nitrogen doses in topdressing (0, 30, 60, 90, and 120 kg ha-1), using seeds inoculated or not inoculated with Azospirillum brasilense. Data were subjected to analysis of variance (ANOVA), comparison of means by Tukey’s test (